The Role of Digital Human Resources Management in Achieving a Competitive Advantage for Organizations: An Applied Study on 6 October University & British University in Egypt - Saleh, Reham (The Arab Journal of Administration, 2022)
The progress of any country in the world is determined by the extent to which it can cope with the technological, administrative and organizational challenges in various fields through transforming the way the work is administered from traditional management practices to computer-based management. Digital technology is considered one of the most important administrative and economic challenges, especially in the development of human resources to be more skilled and efficient in their work roles, besides acquiring more knowledge and ability to perform well within any organization. Therefore, this research is tackling one of the most important topics in electronic human recourse management to show the possibility of benefiting from this practice in supporting human resources management functions as it is considered one of the most important areas that help any organization in achieving a competitive advantage in the market. Managers have been practicing their daily function and tasks in isolation from technological developments in the digital and informational aspects, and today they are facing new challenges that require a new kind of management and performance.